The role of public debt on economic growth with capital loss - Trần, Nhật Thiện (Wiley, 2022)
This paper studies some models in which the “engine of growth” is public debt and capital accumulation. Public debt is assumed to be driven by domestic debt and external debt. The study shows that debt will support economic growth if the initial level of productivity is greater than the cost of investment. In an economy with and without the loss of capital, the article shows the existence of a unique optimal share of investment in physical and human capital and/or new technology. Moreover, if the productivity of the first period is lower than that of a defined threshold value then there exists an optimal level of debt. In addition, if the productivity of the first period is greater than or equal to a defined threshold value, the bigger the debt, the better economies become. Furthermore, this study shows that in an economy with capital loss there is a hidden overhead equivalent to an artificially-augmented interest rate.